Indonesian Foreign Policy: Between National Interests And Global Geopolitical Dynamics - Jerry Sambuaga (Jurnal Mamangan, 2023)
Indonesia's foreign policy has always been based on the principle of "freedom and activity," a normative position that emphasizes non-alignment and participation in building a just and peaceful world order. However, in practice, this principle faces dynamic challenges posed by the complexities of global geopolitics, such as great power rivalry, changes in the international economic order, and multidimensional crises like the pandemic and climate change. This article aims to examine how Indonesia formulates and implements its foreign policy to safeguard national interests, from economic, political, and security perspectives, amidst rapid and uncertain geopolitical change. Using a descriptive qualitative approach and foreign policy analysis, this article finds that Indonesia tends to implement an adaptive-pragmatic strategy that remains grounded in the constitution but is also flexible in responding to global conditions. The principle of "freedom and activity" is not stagnant, but rather undergoes strategic interpretation according to the context of the times and the desired national interests. This study confirms that the success of Indonesian foreign policy depends heavily on its diplomatic ability to maintain a balance between policy autonomy and international engagement